Criminal Liability for Negligence in Traffic that Results in the Loss of Life of Another Person According to Law Number 22 of 2009 (Study of Decision Number 1908/Pid.Sus/2024/PN Medan) - Falentina Gulo; Zetria Erma; Taufika Hidayati (Fox Justi : Jurnal Ilmu Hukum, 2026)
This research aims to analyze the criminal liability for traffic negligence resulting in the loss of life according to Law Number 22 of 2009, identify the causal factors of such negligence, and examine the judge's considerations in imposing a sentence, using Case Decision Number 1908/Pid.Sus/2024/PN Medan as a study. The high number of traffic accidents in Indonesia, predominantly caused by human error, highlights the urgency of this issue. This study employs a normative legal research method with statutory and case study approaches. The findings indicate that the formulation of criminal liability in Article 310 paragraph (4) of Law No. 22 of 2009 is clear, with a maximum threat of 6 years imprisonment. However, its implementation in court decisions often does not reach the maximum penalty, as seen in the Medan District Court ruling where the perpetrator was sentenced to only 2 years and 6 months. Factors causing negligence include human, vehicle, road, and natural factors, with human factors being the most dominant. Judge's considerations are based on juridical, sociological aspects, and trial facts. This research suggests the need for more optimal law enforcement and consistent sentencing to create a deterrent effect.